KARATERISTIK WIRAUSAHA PENDATANG TERHADAP PERILAKU KEWIRAUSAHAAN MASYARAKAT LOKAL DI DESA SUKANAGALIH - Mulyaningrum Mulyaningrum; Dewi Yuliati Indah (Jurnal Riset Bisnis dan Manajemen, 2019)
Cianjur Regency is one of the areas in West Java Province which is an alternative tourism development with a specific local culture. At present, there are many foreign tourists from Middle Eastern countries and many also settled in the area of Sukanagalih Village, Pacet District. As more tourists come to the district, economic activities grow much better as business opportunities for local people according to the market demand. However, there were also many migrants from the Middle East who participated in developing the business together with local communities. This study aims to analyze the influence of the characteristics of migrants from Middle Eastern countries on the business behavior of local communities in Sukanagalih Village. The method used in this study is descriptive and verification. Data collection was done using a questionnaire, supplemented by interviews and observations. The collected data is analyzed using linear regression, correlation, hypothesis test, and coefficient of determination.